Digital light 3D printing of artificial bone with star-shaped polycaprolactone-based polyurethane acrylate - Xinmeng Yang; Shuiwei Qiu; Zhanhui Du; Quansheng Xing (Materials Research Express, 2024)
Advanced medical materials and manufacturing technologies are highly in demand in artificial bones. Herein, a four-arm star-shaped polycaprolactone polyurethane acrylate (FPCLA) was designed and synthesized. The photosensitive character of FPCLA contributed to the rapid prototyping and personalized customization under digital light processing (DLP) 3D printing technology. The FPCLA was prepared by introducing unsaturated double bonds into polycaprolactone tetraethyl alcohol (PCLT). We characterized the physico-chemical properties of the material through FTIR, H-NMR, GPC, DSC and SEM. Cell behaviors on material were observed in vitro . In addition, we employed a DLP 3D printer to evaluate the feasibility of FPCLA to fabricate artificial bone model. The photocuring star polycaprolactone was confirmed in detail by detection method. SEM analyses demonstrated that FPCLA has good tenacity. The material can be used to fabricated artificial bone with a diameter of 3.02 mm at its narrowest by DLP 3D printing technology. The cell survival rates of CCK-8 and Live/Dead fluorescence staining experiments were both above 90%, which indicated safety and feasibility of such new-generation artificial bone made of synthetic polymers.